2009
DOI: 10.1111/j.1439-0272.1982.tb03120.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Lysosomal Enzymes in Flutamide-Induced Stimulation of Rat Testis

Abstract: Zusammenfassung Beteiligung lysosomaler Enzyme bei Flutamid‐induzierter Stimulation des Rattenhodens Das Antiandrogen Flutamid läßt den Plasmaspiegel von LH ansteigen, stimuliert die Steroidbiosynthese im Hoden und hebt die Wirkung von Androgen auf die Zielorgane auf. Flutamid wurde Ratten verabreicht, um die intrazellulären Mechanismen im Hoden zu beobachten, wo die Steroidsyntheserate in Gegenwart des Antiandrogens erhöht war. Das Gewicht der ventralen Prostata sowie der Bläschendrüsen zeigte die antiandroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 15 publications
2
20
0
Order By: Relevance
“…The weights of the testis and epididymis largely dependent on the mass of the differentiated spermatogenic cells and requires continuous androgenic stimulation . It is observed that administration of mancozeb significantly decreased testicular sperm production and epididymal sperm density.…”
Section: Discussionsupporting
confidence: 90%
“…The weights of the testis and epididymis largely dependent on the mass of the differentiated spermatogenic cells and requires continuous androgenic stimulation . It is observed that administration of mancozeb significantly decreased testicular sperm production and epididymal sperm density.…”
Section: Discussionsupporting
confidence: 90%
“…In the testis, acid phosphatase is widely distributed in lysosomes of Sertoli cells, spermatogonia and late spermatids (Chemes, 1986). Activities of free lysosomal enzymes have been shown to rise when testicular steroidogenesis is increased (Mathur & Chattopadhyay, 1982). In this study, the decrease in acid phosphatase activity might reflect decreased testicular function in the treated mice, and therefore, may interfere with the secretion of testosterone.…”
Section: Discussionmentioning
confidence: 87%
“…However, the increased ACP activity has been observed in the liver at the concentration of 200, 250, and 300 mg of T. terrestris extract. Mathur and Chattopadhyay (1982) demonstrated that the activities of phosphatases enzymes have been shown to rise when testicular steroidogenesis is increased.…”
Section: Discussionmentioning
confidence: 97%